QTL Mapping for Seed Germination Response to Drought Stress in Brassica napus - Gad, Mahmoud; Chao, Hongbo; Li, Huaixin; Zhao, Weiguo; Lu, Guangyuan; Li, Maoteng (Frontiers in Plant Science, 2021)
Drought stress is one of the most environmental abiotic stresses that affecting the seed germination and crop growth. In the present study, the genetic characteristics of seed germination under drought stress in a Brassica napus double haploid (DH) population were analyzed. Five germination related indexes, including of germination percentage (GP), root length (RL), shoot length (SL), fresh weight (FW), root to shoot length ratio (R/S) under control and drought stress were calculated, and the drought stress index (DSI) including DSI-GP, DSI-RL, DSI-SL, DSI-FW and DSI-R/S were performed the quantitative trait loci (QTL) analysis based on high-density genetic linkage map. The phenotypic analysis indicated that the R/S is an effective morphological trait in the determination of drought tolerance in seedling stage. Thirty-nine identified QTLs were observed for these traits, then integrated into 36 consensus QTLs, in which 18 QTLs were found to affect the DSI of four traits (GP, RL, SL and R/S). Based on the co-linearity between genetic and physical maps of B. napus, 256 candidate genes were detected, and 128 genes have SNP/InDel variations between two parents, some of which were associated with the drought stress tolerance (for example, BnaC03g32780D, BnaC03g37030D and BnaC09g27300D). The present results laid insights for drought tolerance and its genetic bases in B. napus.